Uji Aktivitas Antioksidan Ekstrak Metanol Daun Pecah Beling Strobilanthes Crispus - Arniah Dali; Haeruddin Haeruddin; Wa Ode Yusmita Miranda; Nasriadi Dali (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2017)
The antioxidant activity test of methanol extracts of the leaves nasty shard Strobilanthes crispus has been done. This study aims to test the phytochemical and antioxidant activity of methanol extracts of the leaves nasty shard Strobilanthes crispus. The leaves nasty shard are macerated with methanol for 3x24 hours. Further methanol extract was tested phytochemically and antioxidant activity by DPPH method (1,1-Diphenyl-2-picrylhydrazil). The result of phytochemical test showed that the methanol extract of the leaves nasty shard Strobilanthes crispus contain secondary metabolites of alkaloids, flavonoids, and saponins. The result of antioxidant activity test showed that the methanol extract of the leaves nasty shard Strobilanthes crispus have antioxidant activity with IC50 of 100,363 ppm.